Low carbon communities : imaginative approaches to combating climate change locally - Peters, Michael D. (Michael Derek), 1975-; Fudge, Shane; Jackson, Tim, 1957- (Cheltenham, UK : Edward Elgar, 2010)
Community participation in fighting climate change is crucial, and the authors here assess the potential for action at the community level as well as some of its limitations. For example, community action offers a significant way to reach global climate targets and bring participants into programs on a relatively personal level, but also has drawbacks in that it can operate contrary to broader programs and constraints. Some topics include: facilitating the low carbon transition, challenges for local level climate change policy and alternative models for low carbon community governance, and models of sustainable and low carbon community activities. Editors Peters, Fudege, and Jackson (RESOLVE, U. of Surrey, U.K), and 17 co-authors contributed to the book.
Community engagement and social organization: introducing concepts, policy and practical applications / Michael Peters -- Sustainable communities: neo-tribalism between modern lifestyles and social change / David Evans -- The social dimensions of behaviour change : an overview of community-based interventions to encourage pro-environmental behaviours / Wokje Abrahamse -- Transforming the nation-state through environmentalism: political influences on a multi-level governance framework in the UK / Shane Fudge -- The role of local authorities in galvanizing action to tackle climate change: a practitioner's perspective / Simon Roberts -- Mobilizing sustainability: partnership working between a pro-cycling NGO and local government in London / Justin Spinney -- Low carbon communities and the currencies of change / Gill Seyfang -- Decarbonising local economies: a new low carbon, high well-being model of local economic development / Elizabeth Cox and Victoria Johnson -- The Community Carbon Reduction Programme / Simon Gerrard -- Global Action Plan's EcoTeams programme / Scott Davidson -- Woking Borough Council: working towards a low carbon community / Lara Curran -- Intentional community carbon reduction and climate change action: from ecovillages to transition towns Joshua Lockyer -- Energy Conscious Households in Action (ECHO Action) / Elliot Bushay -- The HadLOW CARBON Community: behavioural evolution in the face of climate change / Howard Lee and Julie Taylor -- Empowering farmers to react and to act: from an anti golf-course pressure group to a community based farmers' cooperative / Mario Cardona -- Epilogue: Retrofitting buildings viewed as a civil engineering project -- just do it / Michael Kelly.
Includes bibliographical references and index.
Keywords: Environmental policy -- Citizen participation; Environmental protection -- Citizen participation; Climatic changes -- Environmental aspects